Hemorrhage within the tympanic membrane without perforation - Chang-Hee Kim; Jung Eun Shin (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Hemotympanum refers to both the presence of blood in the middle ear cavity and to ecchymosis of the tympanic membrane (TM), and a systematic study of intra-TM (iTM) hemorrhage without bleeding in the middle ear cavity has not been conducted. The goals of our study were to analyze the causes of iTM hemorrhage without TM perforation or bleeding in the middle ear cavity, and to demonstrate the clinical characteristics of the disease. Methods This Case series study included five patients with iTM hemorrhage between August 2014 and August 2017. An iTM hemorrhage was diagnosed when otoendoscopic examination demonstrated minor bleeding behind the intact TM, a hemorrhage was observed between the TM annulus and the epidermal layer, and temporal bone computed tomography revealed thickening of the TM without soft tissue density within the tympanic cavity or temporal bone fracture. Initial symptoms, and serial findings of otoendoscopy and pure tone audiometry (PTA) were investigated. Results iTM hemorrhage developed due to blunt head trauma in two patients, descent barotrauma during scuba diving in two patients, and spontaneous epistaxis in one patient. Otalgia and ear fullness were the most common symptoms, but PTA showed no or minimal conductive hearing loss in all patients. Conclusions An iTM hemorrhage may develop after blunt head trauma, barotrauma due to scuba diving, or spontaneous epistaxis; otological symptoms included otalgia, tinnitus, and aural fullness. An iTM hemorrhage resolved spontaneously without specific treatment, usually within 1 month.